KEABSAHAN HONORARIUM ADVOKAT DALAM MENANGANI KASUS TINDAK PIDANA PENCUCIAN UANG - Sayyid Mahfudh Zikri; Dahlan Ali; Suhaimi Suhaimi (Jurnal Ilmu Hukum, 2016)
Abstract: Advocates including noble profession because it provides such services be giving advice and legal counsel for and on behalf of his client about a case. A lawyer assigned to assist his clients naturally obtain payment for his services (legal fee or honorarium). This study aims to determine the validity of the fees lawyers are derived from money laundering and know the standard fee arrangements in the Advocate Law. This study was a descriptive analytical approach normative juridical aspects. Primary data were collected through a review of the literature relevant to the discussion of the thesis. Secondary data was collected through interviews with informants. The collected data is processed and analyzed by descriptive qualitative and then compared. Based on the results of research and discussion, the setting of the fees lawyers are derived from money laundering included in the explanation of Article 5 Money Laundering Law. Therefore, discussion of the advocate who received honorarium from clients domiciled defendant TPPU cases, so in this case must be tested and assessed using the parameters of their errors as well as the ability to be responsible. Moreover, the Advocate Law stipulates that lawyers who defend clients, both inside and outside the court is entitled to receive fees or honoraria. This is related to retention rights, namely the right to not return the papers held before the honorarium paid in advance. Including using the right to threaten retention and reduce capacity as an advocate in defending and protecting its clients.Keywords : Legal free, honorarium, advocate, money laundering. Abstrak: Advokat termasuk profesi mulia karena memberikan jasa berupa menjadi pemberi nasehat dan kuasa hukum untuk dan atas nama kliennya tentang suatu perkara. Seorang advokat yang bertugas membantu kliennya sudah sewajarnya memperoleh pembayaran untuk jasanya (legal fee atau honorarium). Penelitian ini bertujuan untuk mengetahui keabsahan honor advokat yang bersumber dari tindak pidana pencucian uang dan mengetahui pengaturan honornya dalam UU Advokat. Penelitian ini bersifat deskriptif analitis dengan menggunakan pendekatan aspek yuridis normatif. Pengumpulan data sekunder dilakukan melalui penelaahan kepustakaan yang relevan dengan pembahasan tesis. Sedangkan data primer dikumpulkan melalui wawancara dengan informan. Data yang terkumpul diolah dan dianalisis secara deskriptif kualitatif dan kemudian dikomparasikan. Berdasarkan hasil penelitian dan pembahasan, pengaturan mengenai honor advokat yang bersumber dari tindak pidana pencucian uang termasuk dalam penjelasan Pasal 5 UU TPPU. Oleh karena itu, pembahasan mengenai advokat yang menerima honorarium dari klien yang berkedudukan sebagai terdakwa kasus TPPU, maka dalam hal ini harus diuji dan dikaji menggunakan parameter adanya kesalahan serta kemampuan untuk bertanggung jawab. Selain itu, UU Advokat mengatur bahwa advokat yang membela klien, baik di dalam maupun di luar sidang pengadilan berhak menerima uang jasa atau honorarium. Hal ini berhubungan dengan hak retensi, yakni hak untuk tidak mengembalikan surat-surat yang dipegang sebelum honorariumnya dilunasi terlebih dahulu. Termasuk menggunakan hak retensi untuk mengancam dan mengurangi kapasitas sebagai advokat dalam membela dan melindungi kliennya.Kata kunci : Keabsahan, honorarium, advokat, pencucian uang.